Scaling up the training of teachers through digitalization: the case of the aeioTU network - López, Maria Adelaida; Vila-Villasante, Enric; Quintero, Nehyi (Frontiers in Education, 2023)
The use of digital platforms opens up the possibilities to scale up and strengthen interventions in the field of early childhood development, but also entails challenges regarding engagement, connectivity, or digital literacy. In this paper, we describe and critically assess the use of Monitoring, Evaluation, and Learning (MEL) to guide the process of digitalization undergone by aeioTU, a well-established Colombian organization working in the early childhood development ecosystem, to improve and scale up their educational practices. We reflect from the organization’s perspective on two phases of this process: the creation of a digital learning community to share aeioTU’s educational knowledge and experience, and the expansion of this learning community to become a network aimed towards the development of collaborative relationships and the co-creation of knowledge. From a policy viewpoint, three main learnings are obtained from this process: start with the needs from the local communities; use digital tools already available, and embrace technology without compromising the organization’s core values.